Jesus of Nazareth [videorecording (DVD)] - Zeffirelli, Franco; Powell, Robert, 1944-; Bancroft, Anne, 1931-2005; Borgnine, Ernest, 1917-2012; Cardinale, Claudia, 1939-; Cortese, Valentina; Jones, James Earl; Keach, Stacy; Lo Bianco, Tony; Mason, James, 1909-1984; McShane, Ian, 1942-; Olivier, Laurence, 1907-1989; et al. (Artisan Home Entertainment, 2000)
A film depicting the life of Christ from birth through resurrection.